Towards a contingency-based approach to value for community radio. (1st October 2015) - Order, Simon
Community radio in Australia is now well established and considered an important part of the radio sector, however, in today's economically driven world it is at the bottom of the media money pile. In order to argue for its continuing existence, funding and development in an ever-changing media landscape, some means of capturing its value is essential. This article describes the development of a theoretical framework of value for community radio. The content of the framework was achieved by, first, examining, community media/radio literature through five relevant lenses of analysis. Secondly, a subsequent meta-analysis was applied to consolidate the framework. In order to test the utility of the draft theoretical framework of value, three case studies were conducted with different types of community radio stations in Perth, Western Australia. Two primary research methods were used: interviews with staff and audience focus groups. The testing exercise provided a multimodal insight into the values of community radio as reflected in real life practice. The analysis revealed how value was perceived by participants across three stations as personal motivations, and second, that value at individual stations was contingent upon the characteristics of the individual community radio stations.